The Equivalence of Verbal Humor in English â€“ Indonesian Translation of Harry Potter Novel Entitled The Goblet of Fireâ€ - Budiningtyas, Rina; Hartono, Rudi; Mujiyanto, Januarius (The Journal of Educational Development, 2020)
This study is conducted to find out the existences of humor in the Goblet of Fire novel by using Martin’s (2007) and Catanescu and Tom’s (2001) types of humor, the translation equivalence of verbal humor effect according to Koller in Munday (2001). The translation strategies used dealing with translation problems of pun and irony based on Delabatista’s (2004) and Mateo’s theory in Kitanovska-Kimovska and Neshkovska (2016), translation strategies in the case of idioms and non-equivalence at the word level by Baker (1992), and translation techniques used to achieve the translation equivalence by Molina and Albir (2002). The findings reveal that the data contain humor such as pun, sarcasm, clever replies to serious statements, comparison, overstatement, teasing, surprise, self-deprecation, silliness, irony, satire, and replies to rhetorical questions. To tackle the case of pun, the translation strategies used are pun ST direct copied into the TT, pun to non-pun, and non-pun to pun. Meanwhile, in the case of irony, ST irony becomes TT sarcasm, and ST irony becomes TT irony used as the translation strategies. The finding of translation strategies in the case of idioms reveals the use of translation by paraphrase. Regarding the translation techniques used as they play an important role in affecting the result of the translation product are literal translation (30%), borrowing (25%), adaptation (8.75%), modulation (8.75%), and variation (8.75%), linguistic compression (7.5%), established equivalent, and linguistic amplification (2.5%) for each, amplification, calque, transposition, couplet, triplet successively occupied the same percentage (1.25%). In an attempt to achieve the translation equivalence, the researcher tries to implement five types of equivalence proposed by Werner Koller. The findings are pragmatic equivalence (51.25%), formal equivalence (37.5%), denotative equivalence (7.5%), connotation equivalence (2.5%), text normative equivalence (1.25%).